Effect of prior treatments on selinexor, bortezomib, and dexamethasone in previously treated multiple myeloma - Mateos, Maria V; Gavriatopoulou, Maria; Facon, Thierry; Auner, Holger W; Leleu, Xavier; Hájek, Roman; Dimopoulos, Meletios A; Delimpasi, Sosana; Simonova, Maryana; Špička, Ivan; Pour, Ludĕk; Kriachok, Iryna; et al. (Journal of hematology & oncology, 2021)
Therapeutic regimens for previously treated multiple myeloma (MM) may not provide prolonged disease control and are often complicated by significant adverse events, including peripheral neuropathy. In patients with previously treated MM in the Phase 3 BOSTON study, once weekly selinexor, once weekly bortezomib, and 40 mg dexamethasone (XVd) demonstrated a significantly longer median progression-free survival (PFS), higher response rates, deeper responses, a trend to improved survival, and reduced incidence and severity of bortezomib-induced peripheral neuropathy when compared with standard twice weekly bortezomib and 80 mg dexamethasone (Vd). The pre-specified analyses described here evaluated the influence of the number of prior lines of therapy, prior treatment with lenalidomide, prior proteasome inhibitor (PI) therapy, prior immunomodulatory drug therapy, and prior autologous stem cell transplant (ASCT) on the efficacy and safety of XVd compared with Vd. In this 1:1 randomized study, enrolled patients were assigned to receive once weekly oral selinexor (100 mg) with once weekly subcutaneous bortezomib (1.3 mg/m2) and 40 mg per week dexamethasone (XVd) versus standard twice weekly bortezomib and 80 mg per week dexamethasone (Vd). XVd significantly improved PFS, overall response rate, time-to-next-treatment, and showed reduced all grade and grade ≥ 2 peripheral neuropathy compared with Vd regardless of prior treatments, but the benefits of XVd over Vd were more pronounced in patients treated earlier in their disease course who had either received only one prior therapy, had never been treated with a PI, or had prior ASCT. Treatment with XVd improved outcomes as compared to Vd regardless of prior therapies as well as manageable and generally reversible adverse events. XVd was associated with clinical benefit and reduced peripheral neuropathy compared to standard Vd in previously treated MM. These results suggest that the once weekly XVd regimen may be optimally administered to patients earlier in their course of disease, as their first bortezomib-containing regimen, and in those relapsing after ASCT.Trial registration: ClinicalTrials.gov (NCT03110562). Registered 12 April 2017. https://clinicaltrials.gov/ct2/show/NCT03110562 .
Keywords: Multiple myeloma; Triazoles; SINE compound; dexamethason; Male; Hydrazines; bortezomib; triazoly; Antineoplastic Combined Chemotherapy Protocols; Dexamethasone; Multiple Myeloma; mužské pohlaví; Selinexor; Bortezomib; Exportin-1; lidé; hydraziny; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; mnohočetný myelom; Female